Efficacy and safety of different therapies of non-steroidal anti-inflammatory drugs against antibiotic monotherapy in the treatment of uncomplicated lower urinary tract infection: A systematic review. (September 2022) - Gautam, Sandesh; Shrestha, Rajeev; Ghani, Mohammad R; Ali, Mahmoud M; KC, Manish; Elfert, Yomna A; Chong, Vanessa; Adegbite, Bayode Romeo
This systematic review aimed to evaluate the efficacy of different non-steroidal anti-inflammatory drugs therapy (monotherapy or combined with antibiotics) against antibiotics monotherapy to understand the possible role of non-steroidal anti-inflammatory drugs in managing uncomplicated urinary tract infections and reduce overall antibiotic prescription. We searched four databases: PubMed, EMBASE, Scopus, and Cochrane CENTRAL. We included randomized controlled trials, which had included non-pregnant females above 18 years, published from 2010 to 2020 AD in the English language. We assessed risk of bias (ROB) using COCHRANE ROB version 2.0. We synthesized the conclusion from low ROB studies. Among five included studies, four studies compared non-steroidal anti-inflammatory drugs monotherapy against antibiotics monotherapy, and one study compared non-steroidal anti-inflammatory drugs + antibiotic therapy against antibiotic monotherapy. All studies with low ROB showed significantly higher events of symptom resolution by day 7 with antibiotic monotherapy compared to non-steroidal anti-inflammatory drugs monotherapy. Overall, adverse events were not significantly different in two of three low risk of bias studies; however, one study reported significantly higher adverse effects with non-steroidal anti-inflammatory drugs. Non-urinary tract infection–related adverse events were more common than urinary tract infections–related adverse events in both non-steroidal anti-inflammatory drugs and antibiotic groups. Urinary tract infection–related adverse events were higher in the non-steroidal anti-inflammatory drugs group compared to antibiotics. For every 20–60 participants treated, one would develop pyelonephritis additionally in non-steroidal anti-inflammatory drugs compared to antibiotics. Antibiotics were superior to non-steroidal anti-inflammatory drugs for treating uncomplicated lower urinary tract infections. However, further studies regarding the characteristics of patients likely to develop pyelonephritis on non-steroidal anti-inflammatory drugs monotherapy, and the effectiveness and safety of a combination of non-steroidal anti-inflammatory drugs and antibiotics therapy are essential to reduce the burden of antibiotics and their associated problems.